Answer:
x=3, y=10
Step-by-step explanation:
in triangle KLN all the angles are equal making it an equilateral trianlge. GIven one side being 6, we know all the sides are 6 including the side with the expression y-4.
this means
y-4=6
y=10
Using the converse of the base angles theorem(meaning we know the base angles are congruent so the two sides are conguent), we know that
6=x+3
x=3
|-11+8|=|-3|=3. Plug in f(-11)
Answer:
Step-by-step explanation:
They have to correlate to each other
<span />
So you have to simplify
(9 x 10 x 18) 2 + (5 x 10 x 18) (-7) + (5 x 9 x 18)
(-11) + (5 x 9 x 10)
5 x 9 x 10 x 18
1620 x 2 + 900 (-7) + 810(-11) + 450 x 5
x 5 x 9 x 10 x 18
The answer would be -6/5